PENGEMBANGAN KOMPETENSI DAN ORIENTASI KEWIRAUSAHAAN DALAM MENINGKATKAN KEUNGGULAN BERSAING UMKM DI DESA ANCARAN KECAMATAN KUNINGAN - Rina Masruroh; Yasir Maulana; Munir Nur Komarudin (ABISATYA DINAMIKA ISWARA PUBLISHING, 2025)
This community service program aimed to enhance the entrepreneurial competence and orientation of Micro, Small, and Medium Enterprises (MSMEs) in strengthening their competitive advantage in Ancaran Village, Kuningan District. The primary issues faced by local MSMEs included a limited understanding of structured business planning, low utilization of digital marketing, and a lack of awareness regarding business legality. Through a participatory approach and practice-based training methods, participants were equipped with knowledge and skills related to the preparation of the Business Model Canvas (BMC), digital marketing strategies, and legal aspects of business operations. Evaluation was conducted using pre-tests and post-tests to assess the improvement in participants' understanding. The results showed a significant increase in knowledge and skills, with the average post-test scores rising by 34.9 points compared to the pre-test. These findings indicated that the program contributed positively to improving the readiness of MSMEs to compete more professionally and sustainably. The program also fostered collective awareness of the importance of innovation, digitalization, and legality as fundamental pillars of MSME competitiveness at the local level.